IL-23 inhibitor enhances the effects of PTEN DNA-loaded lipid nanoparticles for metastatic CRPC therapy - Chen, Xinlu; Gong, Luyao; Wang, Yuanyuan; Ye, Chen; Guo, Huanhuan; Gao, Shen; Chen, Jiyuan; Wang, Zhuo; Gao, Yuan (Frontiers in Pharmacology, 2024)
Metastatic castration-resistant prostate cancer (mCRPC) patients face challenges due to limited treatment options. About 50% of patients with mCRPC have functional loss of phosphatase and tensin homology deleted on chromosome 10 (PTEN), which leads to tumor progression, metastasis and immune suppression. Moreover, elevated IL-23 produced by myeloid-derived suppressor cells (MDSCs) was found in CRPC patients, driving tumor progression. Therefore, a combination strategy based on PTEN restoration and IL-23 inhibition may block CRPC progression and metastasis. Here, we developed lipid nanoparticles (LNPs) for PTEN DNA delivery (LNP@PTEN), The LNP@PTEN exhibited high tumor accumulation resulting in increased PTEN expression and efficacy which ameliorated tumor growth and reactivated the anticancer immune system with safety. Further, the combination of LNP@PTEN with Apilimod, an IL-23 inhibitor, exhibited enhanced inhibition of tumor growth, invasion, and metastasis (particularly secondary organ metastasis), which may be attributed to the PTEN function restoration as well as reversing the immunosuppression in tumor environment by decreasing MDSCs and increasing the CD8 + /CD4 + T cell ratio. These findings highlight the potential of LNPs for delivering gene therapeutic agents, and this combinational strategy opens new avenues for the treatment of mCRPC.